2020
DOI: 10.1016/j.jns.2020.116871
|View full text |Cite
|
Sign up to set email alerts
|

Venous cerebral thrombosis in COVID-19 patient

Abstract: Recently considerable attention has been given to a common complication of patients with COVID-19 infection such as the disseminated intravascular coagulation (DIC), especially observed in critically ill COVID-19 patients.We report the description of a patient with COVID-19 who developed thrombosis of the superior vena cava, pulmonary artery and deep intracerebral venous thrombosis. This case demonstrates that extending imaging from the chest to the brain district can be useful in identifying possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 5 publications
1
57
1
2
Order By: Relevance
“…Other three studies described the cases of ischemic stroke concomitant with COVID-19: the patient reported by Co and colleagues [25] was a 62-year-old woman with several pre-existing pathologies such as hypertension, diabetes, dyslipidemia and transient ischemic attack; the patient reported by Frisullo and colleagues [33] was a young woman with no concomitant pathologies, while Zhai and colleagues' [62] patient was a 79-year-old-man. Cerebrovascular complications caused by SARS-CoV-2 infection were also reported by Garaci and colleagues [35]. The authors described a 44-year-old woman with negative past medical history, who developed thrombosis of the superior vena cava, pulmonary artery and deep intracerebral venous thrombosis.…”
Section: Effects Of Sars-cov-2 On Cnsmentioning
confidence: 64%
“…Other three studies described the cases of ischemic stroke concomitant with COVID-19: the patient reported by Co and colleagues [25] was a 62-year-old woman with several pre-existing pathologies such as hypertension, diabetes, dyslipidemia and transient ischemic attack; the patient reported by Frisullo and colleagues [33] was a young woman with no concomitant pathologies, while Zhai and colleagues' [62] patient was a 79-year-old-man. Cerebrovascular complications caused by SARS-CoV-2 infection were also reported by Garaci and colleagues [35]. The authors described a 44-year-old woman with negative past medical history, who developed thrombosis of the superior vena cava, pulmonary artery and deep intracerebral venous thrombosis.…”
Section: Effects Of Sars-cov-2 On Cnsmentioning
confidence: 64%
“…Another pathway for platelet activation in COVID-19 is via the altered ACE1/ACE2 function. Bradykinin is cleaved by ACE1 into metabolites such as vasoactive bradykinin (1)(2)(3)(4)(5)(6)(7)(8) and des-Arg9-bradykinin that are further degraded by ACE2. In the absence of ACE2, des-Arg9-bradykinin accumulation can activate both neutrophils and platelets into an inflammatory phenotype [108].…”
Section: Platelet Dysfunctionmentioning
confidence: 99%
“…Our case suggests that hypercoagulability and thromboin ammation associated with COVID-19 [5] may cause CVT in the late phase of infection, a few weeks after the onset of mild respiratory symptoms. In the last month, a few cases of COVID-19 associated CVT were reported, mostly with fatal or unreported outcome [6][7][8][9][10]. In our case, CVT occurred simultaneously with an asymptomatic internal iliac vein thrombosis and both venous thromboses were effectively treated with intravenous UFH followed by subcutaneous LMWH.…”
Section: Resultsmentioning
confidence: 66%